The Pediatric Anterior Cruciate Ligament Evaluation and Management Strategies (Springer International Publishing, 2018)
This unique book fills the void in the existing literature related to the diagnosis and evaluation of pediatric ACL injuries and presents both current and emerging surgical techniques for pediatric ACL reconstruction. Once considered rare, these injuries are on the rise as children are increasingly active and engaged in high-impact sports. Historically, these injuries have been treated with benign neglect, but there is increasing evidence that non-operative treatment approaches can lead to recurrent instability, further injury to the meniscus or cartilage, and eventually joint degeneration. Opening with discussion of epidemiology, developmental anatomy, and assessment and radiography, this one-stop resource then presents conservative and surgical management strategies and algorithms, including ACL reconstruction without bone tunnels, use of epiphyseal tunnels, trans-physeal tunnels, or hybrid techniques. Special attention is given to the young female athlete, complications, prevention strategies, rehabilitation and return to play considerations. Bringing together the latest clinical evidence with the preferred techniques of experts in the field, The Pediatric Anterior Cruciate Ligament is a comprehensive and detailed analysis of the inherent problems in treating ACL injuries in the pediatric patient, useful for pediatric orthopedic surgeons, orthopedic sports medicine surgeons, primary care sports medicine physicians and other professionals working with the young athlete.